Estrategias para fomentar el hábito de la lectura en los niños de quinto grado de la Escuela de Educación Básica 24 de Febrero. San Francisco ¬ Columbe - Colta – Chimborazo - Gaibor Sangacha, José Vicente (2023)
ABSTRACT: The research places its focus on the importance of developing reading habits in fifth-year students of Basic Education in rural contexts, particularly at the 24 de Febrero School, in Columbe, Colta Canton, Chimborazo. The habit of reading is essential for the comprehensive development of the student, contributing not only to their academic performance, but also to their personal and social development. Despite its relevance, this habit can be especially challenging to grow in rural areas with limited resources. The study used a quantitative approach and correlational, cross-sectional and descriptive design, working with 20 students and 5 teachers. Through surveys and evaluations with rubrics, pre-existing reading habits and the effectiveness of the didactic strategies implemented for their promotion were analyzed. Initially, difficulties in reading habits were identified. However, after the application of the pedagogical strategies, a significant improvement was observed. This demonstrates the effectiveness of the proposed strategies, emphasizing their importance in rural and resource-limited contexts. This research not only benefits current students, but also lays the foundation for future research in the field of education and reading in rural contexts. As a final recommendation, it is urged to implement the strategy guide and to continue research in this field. Keywords: reading habits, didactic strategies, rural education, comprehensive student development